Technical and physical and mathematical education of Ukraine on the way to European integration - Strilkova, T. (New Collegium, 2023)
The urgency of conducting research is dictated by the need to understand ways to improve technical and physical-mathematical education on the way to European integration. The paper analyzes modern aspects of the development of technical and physical-mathematical education in Ukraine and Europe; teaching and assessment methods were analyzed; the level of self-education, self-analysis and self-development of teachers is determined; the impact of stakeholders on the content of modern engineering education is analyzed. The scientific and practical contribution of the Kharkiv National University of Radio Electronics to ensuring the quality of higher technical and physical-mathematical education of Ukraine and its integration into the European educational space is presented. The results of the analysis of the opinion of teachers working in the field of higher technical and physical-mathematical education regarding the organization of the educational process and the connection of higher education with the development of science and production are presented. Based on the identified features of the formation of the educational process in the field of technical and physical-mathematical education, a teaching methodology is proposed that will contribute to the formation of the competences of future specialists in the modern European educational space. The case method is proposed as a synergistic technology in the study of physical, technical and engineering disciplines. The structure of the case method was developed taking into account the integration of science and higher education on the basis of synergistic interaction between a higher educational institution, scientific, research and production organizations.